1995
DOI: 10.1042/bj3110377
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of chitosanase from Streptomyces sp. N174

Abstract: Chitosanase was produced by the strain of Streptomyces lividans TK24 bearing the csn gene from Streptomyces sp. N174, and purified by S-Sepharose and Bio-Gel A column chromatography. Partially (25-35%) N-acetylated chitosan was digested by the purified chitosanase, and structures of the products were analysed by NMR spectroscopy. The chitosanase produced heterooligosaccharides consisting of D-GlcN and GlcNAc in addition to glucosamine oligosaccharides [(GlcN)n, n = 1, 2 and 3]. The reducing- and non-reducing-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
2
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 25 publications
1
82
2
1
Order By: Relevance
“…This mechanism is supported by the fact that microbial family 18 chitinases are unable to cleave the glycosidic bonds of GlcN in partially acetylated chitosan. On the other hand, family 19 chitinases operate by an inverting mechanism (6,17) probably involving the direct attack of the sugar anomeric carbon by a nucleophilic water molecule (35). This mechanism, which has recently been shown to also prevail in a chitosanase (6), does not involve participation of the acetamido group at C-2 and, consequently, allows the hydrolysis of ␤-linked GlcNAc as well as GlcN.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is supported by the fact that microbial family 18 chitinases are unable to cleave the glycosidic bonds of GlcN in partially acetylated chitosan. On the other hand, family 19 chitinases operate by an inverting mechanism (6,17) probably involving the direct attack of the sugar anomeric carbon by a nucleophilic water molecule (35). This mechanism, which has recently been shown to also prevail in a chitosanase (6), does not involve participation of the acetamido group at C-2 and, consequently, allows the hydrolysis of ␤-linked GlcNAc as well as GlcN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that this chitosanase hydrolyzes (GlcN) 6 with inversion of anomeric configuration (31). The average separation between the catalytic residues, expressed as the average of the four distances measured between each pair of carboxylate oxygen atoms, depends upon the mechanism of glycosidase action (29).…”
Section: Resultsmentioning
confidence: 99%
“…chitosan. While this paper was being reviewed, the mechanism of hydrolysis of chitosan by a bacterial chitosanase was reported and indeed found to be inverting [27].…”
Section: Discussionmentioning
confidence: 99%